2021
DOI: 10.1002/cad.20415
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of perceived personal and group ethnic discrimination among secondary school students: The protective role of teacher–student relationship quality and school climate

Abstract: Guided by risk and resilience and attachment perspectives, the present study examined whether teacher–student relationship quality and school climate can buffer against the deleterious effects of perceived personal and group ethnic discrimination on psychological and academic domains. We conducted multilevel analyses of seventh graders (40 classrooms; N = 456; 47% female) with different cultural self‐identifications in Germany. Partially confirming pre‐registered hypotheses, results indicated that high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 74 publications
4
41
0
1
Order By: Relevance
“…Thus, relationship conflict reduces students' creativity. These findings expand those of studies about the negative effect of relationship conflict [11,18,46,47].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, relationship conflict reduces students' creativity. These findings expand those of studies about the negative effect of relationship conflict [11,18,46,47].…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, the results indicated that relationship conflict was negatively correlated with students' creativity (r = −0.590, p < 0.01). Relationship conflict evokes negative emotions and amplifies aggression [13,46,47]. It provokes oppositional behavior regarding personal issues, hostile reactions, and heightens interpersonal tension.…”
Section: Discussionmentioning
confidence: 99%
“…Third, whereas we focused on whether sharing perspectives within an open discussion climate would promote a positive link between classroom diversity and social outcomes, future studies should examine other ways by which teachers can promote positive outcomes of diversity. Promising directions in regard are studies focusing on student-teacher relationships (e.g., Civitillo et al, 2021;Grütter et al, 2021) or on active diversity management by teachers (e.g., Schwarzenthal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To go beyond testing measurement properties and provide evidence for substantive relations, we also test whether foreigner objectification is related to life satisfaction and various aspects of school well-being. Based on studies in Germany showing a link between perceived discrimination and poorer psychological and academic well-being (Kunyu et al, 2020;Brenick et al, 2018;Civitillo et al, 2021;Schachner et al, 2018), we expect that the FOBS will relate negatively to subjective school values, school competence beliefs, and life satisfaction, and positively to behavioral school disengagement. Further, previous studies found that adolescents experiencing greater discrimination tend to adopt a stronger ethnic identity based on the rejection-identification hypothesis (Branscombe et al, 1999;Yip, 2018), which suggests that experiencing rejection from the broader society or others of different ethnic heritage leads to people turning toward their own group to reinforce their self-esteem.…”
Section: Applying and Examining The Foreigner Objectification Scalementioning
confidence: 99%
“…Among German adolescents of migration background more broadly, greater discrimination is related to poorer academic achievement (Schachner et al, 2018). It is also important to highlight that German adolescents of migration background are aware of and resist these experiences of discrimination (Mansel & Spaiser, 2010;, and that the negative effects of discrimination are weakened for adolescents who have a strong connection to their heritage cultural 2 identity (Kunyu et al, 2020), experience a supportive classroom climate (Brenick et al, 2018), and have a positive relationship with their classroom teacher (Civitillo et al, 2021).…”
mentioning
confidence: 99%